Lao People's Democratic Republic : Assessment Letter for the Asian Development Bank and the World Bank. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This note provides an update of the assessment of Lao P.D.R.'s macroeconomic conditions and outlook presented at the time of the 2004 Article IV.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Authority; Outlook; PP; PRGF Arrangement; State Bank; Lao People's Democratic Republic